1993
DOI: 10.1139/z93-178
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the life cycle and morphology of Hysterothylacium aduncum (Rudolphi, 1802) (Nematoda, Ascaridoidea, Anisakidae)

Abstract: Gravid Hysterothylacium aduncum from the intestine of eelpout, Zoarces viviparus, were used as the source of eggs for study. The two first moults occurred in the egg, which does not normally hatch spontaneously. The third-stage larva within the egg was not infective to either fishes or non-crustacean invertebrates, but developed into a typical third-stage larva in Acartia tonsa, harpacticoid copepods, various amphipods, isopods, and mysids. Further development in the fish host was apparently dependent only on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
146
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(164 citation statements)
references
References 16 publications
12
146
0
2
Order By: Relevance
“…Køie (1993), in agreement with Markowski's (1937) There is also a debate about whether L2 (second larval stage) or L3 hatch from the eggs of anisakids. While some authors report that L2 is the stage that hatches (Measures & Hong 1995), others, however, report L3 to be hatching from anisakid eggs (Berry & Cannon 1981, Køie 1993, Køie & Fagerholm 1993, Køie et al 1995. According to observations by Køie (1993) made on Hysterothylacium aduncum, the hatched larvae were of L3, and were ensheathed in the thick, striated cuticle of L2.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Køie (1993), in agreement with Markowski's (1937) There is also a debate about whether L2 (second larval stage) or L3 hatch from the eggs of anisakids. While some authors report that L2 is the stage that hatches (Measures & Hong 1995), others, however, report L3 to be hatching from anisakid eggs (Berry & Cannon 1981, Køie 1993, Køie & Fagerholm 1993, Køie et al 1995. According to observations by Køie (1993) made on Hysterothylacium aduncum, the hatched larvae were of L3, and were ensheathed in the thick, striated cuticle of L2.…”
Section: Resultssupporting
confidence: 85%
“…This L2 cuticle became widely enlarged as a result of the movements of the larva. In the egg, at least 1 larva turned around inside the cuticle, as was also observed by Køie (1993). Our observations have shown that the larvae measure 144 to 215 µm in length, and are surrounded by a 237 to 305 µm-long sheath (n = 10).…”
supporting
confidence: 84%
See 3 more Smart Citations